Nuevas especies de ostrácodos de la Formación Ñirihuau (Oligoceno) en su área tipo (alrededores de San Carlos de Bariloche), provincia de Río Negro, República Argentina (Ameghiniana, 2014)
ive new limnic taxa of Ostracoda are described and illustrated: Chlamydotheca? nirihuauensis sp. nov., Eucypris? barilochensis sp. nov., Candona? mar!uche sp. nov., Eucandonat patagonica sp. nov. and Limnocythere? nahuelhuupiana sp. nov. They are from the Nirihuau Formation of Oligocene age. The salinity of the limnic environment ranges from fresh to oligohaline (0,2- 10%0).The change of the faunal association along severallevels of the succession are attributed to energy variations in the paleoenvironment.